PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH DI DUSUN BERINGIN DESA KALIKOA - azizah al-zahro; Tasya Ul-Haq; Ade Saputra; Muhammad Irhamunna’iem; Achmad Nurjannah (UI Cirebon (Universitas Islam Cirebon), 2023)
Waste management in the dusun beringin of Kalikoa village has not been going well, because there has been no socialization about waste management among its residents. The volume of waste increases along with the increasing rate of population growth. KKM Student Activities in an effort to provide education on how to properly and correctly manage waste with the target of increasing public awareness and knowledge, especially the smallest unit, namely the family, to carry out a waste sorting program through the 3R (Reduce, Reuse, Recycle) program and recycle organic and inorganic waste. inorganic. The method of activity used is the socialization of waste sorting (3R) and the use of recycled waste. It is hoped that through this socialization activity, public awareness in the use of waste will increase, they are accustomed to sorting organic and inorganic waste.